Human resource management: models of interaction ("Journal "U". Economy. Management. Finance.", 2019)
In modern conditions, the core of management of any organization are the staff. Human resources have a dualistic nature in the context of the functioning of the organization, as they can be both the object and the subject of management. In this regard, personnel management is a methodology that can bring the organization to a new level of its qualitative state. The article deals with a set of models of personnel management, possible to use by specialists of personnel services.
Keywords: personnel management; personnel Manager; human resources; human potential